m7G5'ppp5'GmptcpUp at the 5' terminus of reovirus messenger RNA. - Faust, M (1975)
In the presence of S-adenosyl methionine the 5' terminal guanosine residue of in vitro synthesized reovirus mRNA becomes methylated at the 2'-OH position. In addition, 7-methyl guanylic acid is condensed covalently at the 5' terminus resulting in the formation of a 5' to 5' triphosphate bridge. Analysis of the 5' terminal sequence of methylated reovirus mRNA revealed that it has the structure m7G5'ppp5'GmpCpUp.